Who chokes under pressure? The Big Five personality traits and decision-making under pressure. (February 2015) - Byrne, Kaileigh A.; Silasi-Mansat, Crina D.; Worthy, Darrell A.
Highlights: We test the effect of personality on decision-making under pressure. Pressure manipulations involved social and combined social and time pressure. Neuroticism was associated with impaired decision-making under pressure. Agreeableness also negatively predicted decision-making performance. Personality can predict who chokes under pressure during decision-making. Abstract: The purpose of the present study was to examine whether the Big Five personality factors could predict who thrives or chokes under pressure during decision-making. The effects of the Big Five personality factors on decision-making ability and performance under social (Experiment 1) and combined social and time pressure (Experiment 2) were examined using the Big Five Personality Inventory and a dynamic decision-making task that required participants to learn an optimal strategy. In Experiment 1, a hierarchical multiple regression analysis showed an interaction between neuroticism and pressure condition. Neuroticism negatively predicted performance under social pressure, but did not affect decision-making under low pressure. Additionally, the negative effect of neuroticism under pressure was replicated using a combined social and time pressure manipulation in Experiment 2. These results support distraction theory whereby pressure taxes highly neurotic individuals' cognitive resources, leading to sub-optimal performance. Agreeableness also negatively predicted performance in both experiments.